Bomb radiocarbon reveals keratin growth dynamics in loggerhead (Caretta caretta) and green (Chelonia mydas) turtles - Bethan Linscott; Amy A. Wallace; Lorena Becerra-Valdivia; Matt R. P. Harris; Alexandra L. Fireman; Jenna D. Bennett; William F. Patterson; Hannah B. Vander Zanden (Marine Biology, 2026)
Incrementally formed biological tissues can serve as archives of biochemical information pertaining to the life histories of organisms. The sequential isotopic analysis of marine turtle scute keratin is increasingly used for ecological reconstruction, but the timescales represented by these tissues remain poorly understood. Here, we present a method to establish scute growth rates using sequential radiocarbon ( 14 C) measurements on samples taken from loggerhead ( Caretta caretta ) and green turtles ( Chelonia mydas ) stranded along the Florida coast. Using a Δ 14 C coral-otolith reference series and a Bayesian modelling approach, we reconstructed the rate of keratin formation in 24 individuals (representing 120 radiocarbon measurements) and detected synchronous declines in scute growth rates that may be linked to marine environmental stress. Our results provide a chronological framework for the ecological interpretation of biogeochemical data from green and loggerhead turtle scutes and demonstrate the potential for 14 C analysis to investigate the growth dynamics of other incremental tissues.